1988
DOI: 10.1093/bja/61.4.475
|View full text |Cite
|
Sign up to set email alerts
|

The Lower Oesophageal Sphincter in the First Trimester of Pregnancy: Comparison of Supine With Lithotomy Positions

Abstract: Measurement were made of gastric pressure (GP), lower oesophageal sphincter pressure (LOSP) and barrier pressure (BrP) in the supine and lithotomy positions in 17 healthy women undergoing termination of pregnancy in the first trimester. Values in the supine position were similar to those seen in non-pregnant subjects, but there was a significant reduction in LOSP and BrP in the lithotomy position unrelated to any change in intragastric pressure. It is concluded that the lithotomy position is associated with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Recent research has reported disturbances in the myoelectric, mechanical, and motor properties and activities of the GI smooth muscle during pregnancy (4,5,6,7,8,9,10,11,12). Still, the precise mechanism for such gut effects is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has reported disturbances in the myoelectric, mechanical, and motor properties and activities of the GI smooth muscle during pregnancy (4,5,6,7,8,9,10,11,12). Still, the precise mechanism for such gut effects is poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…There is an accumulating body of evidence to suggest that the myoelectric and motor activities of the GI smooth muscle are disturbed during pregnancy. In support of this suggestion, it has been found that pregnancy is associated with decreased gallbladder contractivity (4, 5), lowered esophageal sphincter pressure (6,7,8), reduced gastric emptying (9, 10), and reduced small intestinal (11) and colonic transit times (12). However, the exact molecular mechanisms for such pregnancy-associated GI disorders are still poorly understood.…”
Section: Introductionmentioning
confidence: 85%
“…Non-perfused manometry was carried out to measure LOSP and GP. The principle of manometry was similar to that used in other studies using non-perfused manometry (Cotton and Smith, 1984, Jones, et. al., 1988, Jones, et.…”
Section: Manometrymentioning
confidence: 99%
“…Υπαίτια για αυτές τις ανατομικές ή φυσιολογικές μεταβολές θεωρούνταν η αύξηση του μεγέθους της κυοφορούσας μήτρας (Nagler & Spiro 1961, Dodds et al 1978, Fisher et al 1978α, Fisher et al 1978β, Ulmsten & Sundström 1978, Baron & Richter 1992 (Hey et al 1977, MacLennan 1986, Jones et al 1988, Baron & Richter 1992, Baron et al 1993. Χαρακτηριστικό της σοβαρότητας της κατάστασης είναι ότι κρίνεται αναγκαία η διασωλήνωση της τραχείας σε γυναίκες στα τελευταία στάδια της εγκυμοσύνης, ακόμα και σε περιπτώσεις εκτέλεσης χειρουργικών επεμβάσεων περιορισμένης διάρκειας και μικρής επικινδυνότητας (MacLennan 1986, Jones et al 1988). Στις έγκυες γυναίκες που υποβάλλονται σε μαιευτική επέμβαση, οι παράγοντες που προδιαθέτουν σε εισρόφηση γαστρικού περιεχομένου είναι ουσιαστικά οι ίδιοι που προδιαθέτουν και σε ΓΟΠ κατά την κύηση, με την προσθήκη της κατάκλισης και της χορήγησης αναισθητικών φαρμάκων (Baron & Richter 1992, Baron et al 1993.…”
Section: γαστροοισοφαγική παλινδρόμηση κατά την αναισθησίαunclassified